L-shaped prey isocline in the Gause predator-prey experiments with a prey refuge - Křivan, Vlastimil; Priyadarshi, Anupam (Journal of theoretical biology, 2015)
Predator and prey isoclines are estimated from data on yeast-protist population dynamics (Gause et al., 1936). Regression analysis shows that the prey isocline is best fitted by an L-shaped function that has a vertical and a horizontal part. The predator isocline is vertical. This shape of isoclines corresponds with the Lotka-Volterra and the Rosenzweig-MacArthur predator-prey models that assume a prey refuge. These results further support the idea that a prey refuge changes the prey isocline of predator-prey models from a horizontal to an L-shaped curve. Such a shape of the prey isocline effectively bounds amplitude of predator-prey oscillations, thus promotes species coexistence.
Keywords: Animals; biologické modely; predátorské chování; Models, Biological; zvířata; Predatory Behavior; Paramecium; Schizosaccharomyces